2012
DOI: 10.2174/1874331501206010001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Amendment Application on Soil Quality and Garlic Yield in Central-Western Argentina

Abstract: Abstract:We analyzed during two garlic crop cycles, the effects of chicken manure and vermicompost on soil chemical and biological properties in an agricultural farm irrigated with municipal wastewater of central-western Argentina. Also we evaluate garlic yield and possible health risks as resulting from the organic amendments and the wastewater use. We found that: a) different doses and types of amendments did not have any significant effects on soil fertility; b) chicken manure and soil before planting, had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…1). Poultry manure and vermicompost are good sources of nutrients [41][42][43] and might provide more substrates for utilization by the microorganisms, due to this maximum metabolic activity that was observed in the present investigation.…”
Section: Discussionsupporting
confidence: 58%
“…1). Poultry manure and vermicompost are good sources of nutrients [41][42][43] and might provide more substrates for utilization by the microorganisms, due to this maximum metabolic activity that was observed in the present investigation.…”
Section: Discussionsupporting
confidence: 58%
“…However, root crop yield response to compost and other organic amendments can be less pronounced relative to grain, fruiting, and vegetative crops (Wortman et al, 2017). Filippini et al (2012) found that 4 Mg ha -1 of vermicompost and chicken litter compost was insufficient for increasing garlic yield, but 8 Mg ha -1 did increase yield compared to a non-fertilized direct soil control. In a different study, a 1:1 mix of soil and vermicompost increased garlic yield nearly three-fold compared to soil alone (Argüello et al, 2006).…”
Section: Crop Yieldmentioning
confidence: 99%
“…They observed that the influence of pigs on ammonia losses appeared to be most pronounced in the latter half of the fattening period, when the pigs excreted maximum amounts of nitrogen. In another investigation, Filippini et al (2012) [6] reported the effect of organic amendments like chicken manure and vermicomposting application on soil quality and garlic yield in central western Argentina. They concluded that to obtain beneficial effects on soil fertility from organic amendment application, wastewater treatment systems must be improved and tillage practice must be reduced.…”
Section: Usda-ars Soybean Genomics and Improvement Laboratory Beltsmentioning
confidence: 99%